2010
DOI: 10.1590/s1413-81232010000900025
|View full text |Cite
|
Sign up to set email alerts
|

Adesão medicamentosa em idosos em seguimento ambulatorial

Abstract: nonadhesion (OR: 7.092). The associated events which better predict the drug non-adhesion were: "living alone" (OR: 4.346) and "side effects" (OR: 8.219).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
30
2
31

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(69 citation statements)
references
References 14 publications
6
30
2
31
Order By: Relevance
“…10 One hypothesis to explain greater adherence to treatment by older individuals is fear of damaging their health and desire to live and the need to follow treatment increases their motivation to follow medical treatment regimes. 3 Factors related to the health and the care of older patients that may affect adherence to treatment include: type, severity and duration of the illness, number of morbidities, frequency with which health care services are used, patient satisfaction with health care professionals and care quality. 13 In this study, no significant difference were found between levels of adherence to treatment and the primary health care model in the area of residence or having had a doctor's appointment in the preceding three months.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…10 One hypothesis to explain greater adherence to treatment by older individuals is fear of damaging their health and desire to live and the need to follow treatment increases their motivation to follow medical treatment regimes. 3 Factors related to the health and the care of older patients that may affect adherence to treatment include: type, severity and duration of the illness, number of morbidities, frequency with which health care services are used, patient satisfaction with health care professionals and care quality. 13 In this study, no significant difference were found between levels of adherence to treatment and the primary health care model in the area of residence or having had a doctor's appointment in the preceding three months.…”
Section: Resultsmentioning
confidence: 99%
“…The cost of treatment, therefore, is shown to be an important factor in adherence to treatment in this segment of the population. 5 In an outpatient based study that took place in Campinas, SP, Southeastern Brazil, 3 the lack of medication in primary health care units and spending on medicines were highlighted by the older adults interviewed as the main difficulties in acquiring medicine. This finding emphasizes the importance of appropriate pharmaceutical care management in primary health care as a facilitator of access to medications at this level of care, which could impact on adherence to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…For older adults, instruments and guidelines to prevent and recognize communication impairments and technologies to facilitate adherence to treatment should be used (20) . These competencies for older adults are necessary considering their sensory and movement changes that have a high potential to impair communication.…”
Section: For This Reason It Is Important That a Competent Multiprofesmentioning
confidence: 99%
“…A study with 165 elderly patients in outpatient monitoring in a university hospital about the reasons for complying with drug treatment revealed the situation of living alone, and the side effects of the drugs are the main predictors for non-compliance to therapy, which, for the authors, shows the relevance of the support provided by other people in the care for this population group (18) .…”
Section: Rev Esc Enfermmentioning
confidence: 93%